Severe early-onset manifestations of generalized arterial calcification of infancy (mimicking severe coarctation of the aorta) with ABCC6 gene variant — Case report and literature review - Fãgãrãşan, Amalia; Gozar, Liliana; Ghiragosian, Simina-Elena Rusu; Murariu, Mircea; Pop, Marian; Crauciuc, Andrei; Miclea, Diana; Şuteu, Carmen Corina (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Generalized arterial calcification of infancy (GACI) is a rare cause of infantile heart failure and systemic hypertension with a poor prognosis, characterized by extensive calcification and proliferation of the intimal layer of large and medium sized arteries. Case report: We present the first case report of successful surgical treatment of severe aortic arch obstruction by calcified plaques mimicking severe coarctation of the aorta and the outcome (of bisphosphonate therapy) in a newborn with GACI. Furthermore, we report the identification of a variant in ABCC6 gene, possibly associated with severe early-onset manifestations of GACI. Conclusion: This case report highlights the importance of considering GACI in an infant with heart failure and echo-genic vessels on echocardiography as well as any radiological study.